2023
DOI: 10.7554/elife.78397
|View full text |Cite
|
Sign up to set email alerts
|

Infant brain regional cerebral blood flow increases supporting emergence of the default-mode network

Abstract: Human infancy is characterized by most rapid regional cerebral blood flow (rCBF) increases across lifespan and emergence of a fundamental brain system default-mode network (DMN). However, how infant rCBF changes spatiotemporally across the brain and how the rCBF increase supports emergence of functional networks such as DMN remains unknown. Here, by acquiring cutting-edge multi-modal MRI including pseudo-continuous arterial-spin-labeled perfusion MRI and resting-state functional MRI of 48 infants cross-section… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
9
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

3
3

Authors

Journals

citations
Cited by 9 publications
(24 citation statements)
references
References 71 publications
(127 reference statements)
2
9
0
Order By: Relevance
“…Our findings were further supported by a validation analysis of voxel-wise age effects using rCBF maps ( N = 48) obtained from cohort-2 (Beijing site) 30 . The age effects were highly reproducible in both infant rCBF datasets, showing similar spatial topographies (Supplementary Fig.…”
Section: Resultssupporting
confidence: 72%
See 3 more Smart Citations
“…Our findings were further supported by a validation analysis of voxel-wise age effects using rCBF maps ( N = 48) obtained from cohort-2 (Beijing site) 30 . The age effects were highly reproducible in both infant rCBF datasets, showing similar spatial topographies (Supplementary Fig.…”
Section: Resultssupporting
confidence: 72%
“…9 . The identified physiological hierarchy aligns well with the pronounced and qualitatively distinct regional differences in infant functional connectivity 2022,30 , neuroanatomy 2,16,43 , and transcriptomic profile 44,45 . For instance, limbic and primary sensorimotor functional networks are relatively well established at birth 20,21 .…”
Section: Discussionsupporting
confidence: 67%
See 2 more Smart Citations
“…Similarly, two recent, large sampled fMRI studies of newborns found evidence of DMN connectivity mere weeks after birth (Hu et al, 2022;Sylvester et al, 2022). Furthermore, increasing functional connectivity within the DMN is supported by increases in regional cerebral blood flow in the first two years of life (Yu et al, 2023). The DMN present during the perinatal period might be interpreted as a weaker, immature version of the adult DMN, as Hu et al (2022) found that the neonatal DMN and other fMRI networks had less within-network connectivity compared to adults.…”
Section: Weak Fields and Strong Fields: What Mri Adds To The Picturementioning
confidence: 75%